Das Metro-System von Singapur - Benchmark für andere Länder? - Aberle, Gerd (Deutscher Verkehrs-Verl., 2009)
Der Stadtstaat Singapur mit 4,3 Mio. Einwohnern auf einer Fläche von 581 km2 besitzt neben einer relativ hohen Fahrzeugdichte im Zentrum ein hervorragend ausgestattetes Nahverkehrssystem. Dieses stützt sich neben einem weit gefächerten Busangebot vor allem auf ein weltweit als Benchmark anzusehendes schienengebundenes Metro-System. Es gliedert sich in mehrere technisch unterschiedliche Teilsysteme und stellt das Rückgrat einer qualitativ sehr hochwertigen ÖPNV-Mobilität dar. Es ist beeindruckend, dieses System in seinen wesentlichen Merkmalen zu analysieren.

With a total population of 4.3 m, Singapore figures prominently among the most densely inhabited land areas. Local public transport has to cope with a high volume of traffic throughout the day, based on a diverse system of bus routes and especially the ultra modern, attractive Mass Transport Rail (MRT) system. Metro carriages and stations are air conditioned. Together with an electronic ticketing system and proper regulations, absolute cleanliness and security ensure a high degree of user-quality. The Met system has undergone continuous expansion since 1987, and the route network is planned to double in extent by 2020. Complementary to the MRT system, the narrow gauge Light Rail System (LRT) provides feeder services with mini metros to a high-frequency regular-interval schedule. The system's numerous investive and organizational controls are rather exceptional but some of them are considered unsuitable for Europe.
Singapore's Metro System - a model for other countries?
Keywords: Öffentlicher Verkehr; Personenverkehr; Nahverkehrssystem; ÖPNV; Schienenpersonenverkehr; U-Bahn; Verkehrsmittelwahl; Stadtverkehr; Verkehrstechnologie; Ticketing; Verkehrsangebot